Resistance of freshwater sediment bacterial communities to salinity disturbance and the implication for industrial salt discharge and climate change-based salinization - Tammert, Helen; Kivistik, Carmen; Kisand, Veljo; Käiro, Kairi; Herlemann, Daniel P. R. (Frontiers in Microbiomes, 2023)
The impact of salinization on freshwater ecosystems became apparent during the recent ecological disaster in the Oder River (2022) caused by salt discharge from mining activities. How bacterial communities respond to salinization caused by industrial salt discharge, or climate change driven events depends on the sensitivity of these complex bacterial communities. To investigate the sensitivity to pulse salinization on bacterial communities we performed an experiment in the salinity range from 0.2 to 6. In addition, we sampled similar salinities in the littoral zone of the Baltic Sea where the bacterial communities are permanently exposed to the respective salinities. To simulate a major disturbance, we included ampicillin/streptomycin treatment in the experiment. While the addition of antibiotics and increase in salinity had a significant impact on the water bacterial richness and community composition, only antibiotics affected the sediment bacterial community in the experiment. In contrast, sediment bacterial communities from the Baltic Sea littoral zone clustered according to salinity. Hence, sediment bacterial communities are more resistant to pulse changes in salinity than water bacteria, but are able to adapt to a permanent change without loss in species richness. Our results indicate that moderate pulse salinization events like industrial salt discharge or heavy storms will cause changes in the water bacterial communities with unknown consequences for ecosystem functioning. Sediment bacterial communities however will be probably unaffected in their ecosystem services depending on the disturbance strength. Long term disturbance like sea level rise or constant salt discharge will cause permanent changes in the sediment bacteria community composition.